2011
DOI: 10.1253/circj.cj-11-0497
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Rosuvastatin Improves Arterial Stiffness in High-Risk Japanese Patients With Dyslipdemia in a Primary Prevention Group - A Comparison With Fluvastatin -

Abstract: Background:The treatment effects of rosuvastatin on arterial stiffness were assessed and compared to those of fluvastatin in high-risk Japanese patients with dyslipidemia in a primary prevention group. Methods and Results:Patients were randomly assigned to either 2.5-5 mg/day of rosuvastatin (Group A) or 20-40 mg/day of fluvastatin (Group B) and followed up for 12 months. In Group A (n=38), there was a progressive reduction in brachial-ankle pulse wave velocity (baPWV) along with a decrease in the low-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
13
0
2
Order By: Relevance
“…In adults with CDO, statin therapy has been shown to beneficially alter the standard lipid and LDL particle profiles and to improve multiple measures of vascular function and clinical cardiovascular outcomes. [155][156][157][158][159][160][161][162][163][164][165] In children, statin treatment has been shown to effectively lower LDL-C levels and in a small number of studies, to improve LDL-C subpopulation characteristics on NMR analysis. 166,167 Statins are also known to be antiinflammatory, which may be important in the proinflammatory state associated with obesity.…”
Section: Medication Therapy For Cdomentioning
confidence: 99%
“…In adults with CDO, statin therapy has been shown to beneficially alter the standard lipid and LDL particle profiles and to improve multiple measures of vascular function and clinical cardiovascular outcomes. [155][156][157][158][159][160][161][162][163][164][165] In children, statin treatment has been shown to effectively lower LDL-C levels and in a small number of studies, to improve LDL-C subpopulation characteristics on NMR analysis. 166,167 Statins are also known to be antiinflammatory, which may be important in the proinflammatory state associated with obesity.…”
Section: Medication Therapy For Cdomentioning
confidence: 99%
“…In adults with high TGs and CD, statin therapy beneficially alters the standard lipid and LDL particle profiles and improves vascular function and clinical cardiovascular outcomes [129][130][131]. There are as yet no published studies examining statin effects on vascular measures in youth with high TGs or CD.…”
Section: Statinsmentioning
confidence: 99%
“…A well-known pleiotropic effect of HMG-CoA reductase inhibitors is the inhibition of the synthesis of farnesyl pyrophosphate or geranyl-geranyl pyrophosphate which is an important substrate for progerin formation 56). Some studies reported that statins suppress the progression of arterial stiffening in humans 56)57). More recently, rapamycin, which is an inhibitor of the mammalian target of rapamycin, reportedly may enhance the clearance of mutated lamin by the autophage mechanism (Fig.…”
Section: Molecular Mechanism Of Arterial Ageingmentioning
confidence: 99%